2022
DOI: 10.1111/fwb.13976
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of fish to heatwaves in agricultural streams: What does not kill you makes you stronger?

Abstract: Heatwaves are increasing in frequency and intensity under climate change. Freshwater ecosystems are among the most thermally impacted systems, within which agricultural streams are experiencing the most extreme heatwaves and deserve prioritised focus. Heatwaves are approaching the upper thermal limits of many fishes but have received little attention to date. To study whether and how fish tolerate heatwaves from a physiological perspective, we simulated single, multiple, and extended heatwaves at 32 and 34°C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…, 2018; Dai et al. , 2022). Empirical research has demonstrated that extreme events can drive directional selection toward more resistant phenotypes (Pauls et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2018; Dai et al. , 2022). Empirical research has demonstrated that extreme events can drive directional selection toward more resistant phenotypes (Pauls et al.…”
Section: Discussionmentioning
confidence: 99%
“…As for the differences in acclimation capacity between the populations of the hydrophilid species studied, they might be related to the higher intensity and frequency of extreme events with ongoing climate change, such as heat waves, which could have an impact on the plasticity of the upper thermal limit at the micro-evolutionary level (Baudier et al, 2018;Dai et al, 2022). Empirical research has demonstrated that extreme events can drive directional selection toward more resistant phenotypes (Pauls et al, 2013; and cause a loss of genetic diversity (e.g., Gurgel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic global warming may lead to seasonal temperature increases by up to 4°C by 2100, along with an increase in the frequency of localized acute and extreme warming events ( Comte and Olden, 2017 ; Bierbach et al, 2022 preprint). These changes are likely to cause population declines, or even extinction of species that are poorly adapted to cope with these novel environmental conditions ( Pacifici et al, 2015 ; Dai et al, 2022 ). A key trait and a critical factor for survival in this regard is an organism's ability to survive and function within a specific temperature range, which is referred to as thermal tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…critical thermal limits, CT min and CT max , ( Beitinger and Lutterschmidt, 2011 )], although growth and reproduction may require a narrower range thus higher minima and lower maxima ( Pörtner, 2001 ; Burleson and Silva, 2011 ; Illing et al, 2020 ). Understanding how organisms deal with increased or even extreme temperature regimes that will become more frequent becomes crucial for predicting the effects of climate change on populations and species, and ultimately may help to take suitable measures and actions to counteract local population declines or extinction events ( Dai et al, 2022 ; Earhart et al, 2022 ; Desforges et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation